Effect of storage media and period on bare root transplanting of aonla (Emblica officinalis Gaertn) budded plants (Indian Journal of Arid Horticulture, 2020)
The present study was carried out to find out appropriate storage medium and period of storage to improve transplanting success of aonla budded plants. There were four storage media (moist gunny bag, sphagnum moss, polythene sheet and polythene sheet + sphagnum moss) and four storage period (control-zero day, 48, 96 and 144 hours). Ten budded plants were transplanted in field at each date at 30 x 30 cm apart replicated thrice. Among different storage media moist gunny bag and sphagnum moss give better performance with respect to budded plants establishment and other growth characters followed by polythene sheet + sphagnum moss equally effective for a period of more than 48 hours in keeping bare rooted budded plants for transplanting The present study was carried out to find out appropriate storage medium and period of storage to improve transplanting success of aonla budded plants. There were four storage media (moist gunny bag, sphagnum moss, polythene sheet and polythene sheet + sphagnum moss) and four storage period (control-zero day, 48, 96 and 144 hours). Ten budded plants were transplanted in field at each date at 30 x 30 cm apart replicated thrice. Among different storage media moist gunny bag and sphagnum moss give better performance with respect to budded plants establishment and other growth characters followed by polythene sheet + sphagnum moss equally effective for a period of more than 48 hours in keeping bare rooted budded plants for transplanting The present study was carried out to find out appropriate storage medium and period of storage to improve transplanting success of aonla budded plants. There were four storage media (moist gunny bag, sphagnum moss, polythene sheet and polythene sheet + sphagnum moss) and four storage period (control-zero day, 48, 96 and 144 hours). Ten budded plants were transplanted in field at each date at 30 x 30 cm apart replicated thrice. Among different storage media moist gunny bag and sphagnum moss give better performance with respect to budded plants establishment and other growth characters followed by polythene sheet + sphagnum moss equally effective for a period of more than 48 hours in keeping bare rooted budded plants for transplanting
Keywords: Budded plants; gunny bag; sphagnum moss; transplanting success